The New Division of Labor : How Computers Are Creating the Next Job Market. - Murnane, Richard J. (Princeton University Press, 2012)
As the current recession ends, many workers will not be returning to the jobs they once held--those jobs are gone. In The New Division of Labor, Frank Levy and Richard Murnane show how computers are changing the employment landscape and how the right kinds of education can ease the transition to the new job market. The book tells stories of people at work--a high-end financial advisor, a customer service representative, a pair of successful chefs, a cardiologist, an automotive mechanic, the author Victor Hugo, floor traders in a London financial exchange. The authors merge thes.